ANALISIS SEMIOTIKA CHARLES S. PIERCE PADA POSTER STREET HARASSMENT KARYA SHIRLEY - Manesti Pangestuti (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2021)
Street harassment often occurs and becomes a problem that worries both the victim and the community. In this regard, the community tries to give an appeal to better understand street harassment which often occurs but is not taken seriously by the law. Shirley's efforts to provide appeals related to sexual harassment on the street were shown through street harassment posters by providing images, forms, and signs of harassment. To find out the overall meaning and message, Pierce's semiotics will be used about representations, objects, and interpretants with a descriptive qualitative approach. The results obtained show that the poster gives a message to the reader to be more careful and alert to harassment which is often ignored. The colors, fonts, pictures, and words on the poster describe in detail the forms of harassment or street harassment.